Local reaction rates and surface diffusion on nanolithographically prepared model catalysts: Experiments and simulations - Libuda, Jörg; et al. (Journal of Chemical Physics, 2005)
Combining molecular beam methods and angular resolved mass spectrometry, we have studied the angular distribution of desorbing products during CO oxidation on a planar Pd/silica supported model catalyst. The model catalyst was prepared by means of electron beam lithography, allowing individual control of particle size, position, and aspect ratio, and was characterized by atomic force microscopy and scanning electron microscopy before and after reaction. In the experiment, both oxygen and CO rich regimes were investigated using separate molecular beams for the two reactants. This allows exploration of diffusion effects of reactants on the particles and of shadowing and backscattering phenomena. A reaction-diffusion model was developed in order to extract information about local reaction rates on the surface of the catalyst nanoparticles. The model takes into account the structural parameters of the catalyst as well as the backscattering of the reactants and products from the support. It allows a quantitative description of the experimental data and provides a detailed understanding of temperature and reactant flux dependent effects. Moreover, information on the surface mobility of oxygen under steady-state reaction conditions could be obtained by comparison with the experimental results.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.ppc20.localr